2009
DOI: 10.4161/cbt.8.9.8186
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase C by Phorbol 12-Myristate 13-Acetate suppresses the growth of lung cancer cells through KLF6 induction

Abstract: Phorbol 12-myristate 13-acetate (PMA) modulates cell proliferation and survival by activating several intracellular signaling pathways. Protein kinase C (PKC) plays a key role in PMA-induced growth arrest of non-small cell lung cancer (NSCLC) cells. Kruppel-like transcription factor 6 (KLF6), which is associated with negative control of cell proliferation, is downregulated in many cancers, including NSCLC. In this study, we found that KLF6 is downregulated in 17 lung cancer cell lines and in cells representing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
(37 reference statements)
1
29
0
Order By: Relevance
“…TPA significantly increases cell proliferation in fibroblasts, epidermal cells, and several cancer cell lines, such as KG-1 human myeloblastic leukemia cells and ZR75-1 human breast cancer cells (22,23). However, TPA-induced activation of PKC suppresses the cell growth of non-small cell lung cancer cells and DanG pancreatic cancer cells (21,24). Although the role of TPA on the regulation of the cell cycle is controversial, we also found that TPA triggers the arrest of S to G2/M transition in MCF-7 and MDA-MB-231 breast cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…TPA significantly increases cell proliferation in fibroblasts, epidermal cells, and several cancer cell lines, such as KG-1 human myeloblastic leukemia cells and ZR75-1 human breast cancer cells (22,23). However, TPA-induced activation of PKC suppresses the cell growth of non-small cell lung cancer cells and DanG pancreatic cancer cells (21,24). Although the role of TPA on the regulation of the cell cycle is controversial, we also found that TPA triggers the arrest of S to G2/M transition in MCF-7 and MDA-MB-231 breast cancer cells.…”
Section: Discussionmentioning
confidence: 74%
“…In this situation, KLF6 expression is induced and contributes to reduce cell proliferation rate, avoiding that it reach aberrant levels. In agreement, PMA-induced growth arrest of nonsmall cell lung cancer cells was mediated by induction of KLF6 expression following PKC activation (24). In addition, KLF6 mediates inhibition of cyclin D 1 /cyclin-dependent kinase 4 (cdk4) activity, resulting in growth inhibition (33).…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 70%
“…Additionally, protein kinase C (PKC) has been associated with KLF6 increase following 12-O-tetradecanoylphorbol-13-acetate (TPA)-mediated growth arrest of nonsmall cell lung cancer cells. Moreover, activation of JNK and p38 pathways in lung cancer cells is downstream effectors for KLF6 protein rise on PKC induction (24). Moreover, regulation of KLF6 transcriptional activity and halflife through direct acetylation (25) and proteasome-mediated degradation (25,26), respectively, have been reported.…”
Section: Discovery Of Klf6: a Key Regulator Of Cell Homeostasis And Dmentioning
confidence: 98%
“…However, PMA itself induces cytokine production by monocytes. Nuclear factor kappa-B (NF-kB) [21,22] and protein kinase C [23] have long been considered to mediate a prototypical proinflammatory signaling pathway, and PMA is a specific activator of both protein kinase C and NF-κB [24][25][26]. PMA induces the phosphorylation of extracellular signal-regulated kinase (ERK), which is dependent on the protein kinase C alpha pathway [27,28].…”
Section: Discussionmentioning
confidence: 99%